Pengaruh Inflasi dan BI Rate terhadap Simpanan Masyarakat pada Bank Umum Pemerintah di Indonesia Tahun 2009-2018 - Ni Made Mareta Dewi Saputri; A. A. Ketut Jayawarsa; I Gusti Ayu Athina Wulandari (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2020)
The research is entitled The Effect of Inflation and BI Rate on Public Savings at Government Commercial Banks in Indonesia on 2009-2018. The formulation of the problem is: How the influence of Inflation and BI Rate on Public Savings at Government Commercial Banks in Indonesia on 2009-2018 simultaneously and partially. The aims of the research is to analyze the effect of Inflation and BI Rate on Public Savings at Goverment Commercial Banks in Indonesia on 2009-2018. Data analysis tools used are the classical assumption test and hypothesis testing with multiple linear regression methods. The result of the research is the Inflation and BI Rate simultaneously (together) had a positive and significant effect on public savings at Government Commercial Bank in Indonesia. Inflation variable partially has a negative and significant effect on public savings, while the BI Rate variable partially has a negative and significant effect on public savings.